Musical Structuring in Mughadhī al-Arwāḥ wa Musallī al-Ashbāḥ by the Poet Al-Tūmī Sa‘īdān - chebli, fatmaa (El Omda in Linguistics and Discourse Analysis, 2018)
It is well known that poetry is one of the most famous, oldest, and widely circulated literary arts, as it has long been the means through which humans express their inner feelings and wanderings of thought. Since popular poetry, like classical Arabic poetry, serves to convey emotions, it does not differ from it in the structure of the poem—composed of lines, verses, stanzas, rhyme, and purposes, including the nostalgic return to ruins. Arabic poetry was widespread among Arab tribes, taking the form of Ahājīz and Arājīz, which Arabs would improvise and recite while tending their camels, as well as songs and chants performed during their celebrations and sorrows. These popular Arabic poems invariably include a musical rhythm that gives them their poetic character. Several artistic forms of popular poetry emerged, the most important of which are: Qurayd (quatrain), Muwashshah, Dūbīt, Mawāliyā, Zajal, Kan Kan, and Qawma. The first three fall under classical Arabic poetry, which follows Arabic traditions and preserves linguistic integrity, while the latter forms belong to popular poetry.